2019
DOI: 10.3390/nu11092086
|View full text |Cite
|
Sign up to set email alerts
|

Food Addiction: Implications for the Diagnosis and Treatment of Overeating

Abstract: With the obesity epidemic being largely attributed to overeating, much research has been aimed at understanding the psychological causes of overeating and using this knowledge to develop targeted interventions. Here, we review this literature under a model of food addiction and present evidence according to the fifth edition of the Diagnostic and Statistical Manual (DSM-5) criteria for substance use disorders. We review several innovative treatments related to a food addiction model ranging from cognitive inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 467 publications
(583 reference statements)
0
48
1
4
Order By: Relevance
“…Belief in this dominant public health model for overweight and obesity is thought to be linked to weight stigma because it infers and/or attributes overweight and obesity to personal responsibility, lack of discipline, and laziness. The FAM explanation for obesity and weight control is garnering attention in several research fields [19,38,39] and is gaining traction in popular culture [40]. Indeed, studies suggest that around 15% of people meet criteria for a food addiction and anywhere from 28-52% of people believe they may be addicted to a food [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Belief in this dominant public health model for overweight and obesity is thought to be linked to weight stigma because it infers and/or attributes overweight and obesity to personal responsibility, lack of discipline, and laziness. The FAM explanation for obesity and weight control is garnering attention in several research fields [19,38,39] and is gaining traction in popular culture [40]. Indeed, studies suggest that around 15% of people meet criteria for a food addiction and anywhere from 28-52% of people believe they may be addicted to a food [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research posits that some people may have a neurobiological addiction to certain foods, particularly ultra-processed hyper-palatable foods. This addiction may, in part, contribute to people's food choices and consumption behaviour, and in turn obesity rates [18,19]. Termed food addiction, neuropsychological and behavioural research on the addictive properties of food identifies considerable overlap in the food and drug reward and addiction-related centres and pathways of the brain; as a result, food can be as rewarding and addictive as other addictive substances such as drugs, which share overlapping brain reward pathways [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…If we focus on specific foods, the person's act of eating, and emotions linked to eating, it seems that two aspects of self-regulatory failure that are particularly pertinent in both substance use and overeating are impulsivity and reward sensitivity [36][37][38]. With respect to impulsivity (a multifaceted construct, it can be defined broadly as "the tendency to think and act without sufficient forethought, which often results in behavior that is discordant with one's long-term goals") [39], it has been implicated in overeating and obesity [40][41][42][43]. Regarding reward sensitivity, a heightened general sensitivity to reward has also been linked to overeating [44][45][46].…”
Section: Food Addiction Eating Addiction and Emotional Eatingmentioning
confidence: 99%
“…Whilst it is in a different disorder, it is however reported that in BED patients planned binges are often longer and larger than initially intended by the patient (Curtis and Davis, 2014). This indicates that a deficit in cognitive control, resulting in a behavioral loss of control, is primarily present during the binge itself (also see Adams et al, 2019). Crucial to all binging disorders is the specific, food-related loss of control during the binge episode itself, as illustrated by an increase in intake, even if the episode is planned beforehand (Curtis and Davis, 2014).…”
Section: Cognitive Controlmentioning
confidence: 99%